Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan CV. Dinasti Jati Furniture Di Bekasi - Prabaswara, Bagas Arif; Siahaan, Matdio; Anas, Haryudi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The Effect of Work Motivation and Compensation on Employee Productivity CV. Dinasti Jati Furniture in Bekasi. This study aims to analyze the effect of work motivation and compensation on employee productivity CV. Dinasti Jati Furniture in Bekasi. The research employed a quantitative approach using a survey method with questionnaires distributed to 110 respondents, who were employees from the production and finishing divisions with more than one year of service. The independent variables in this study are work motivation and compensation, while the dependent variable is work productivity. Data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that work motivation significantly influences employee productivity, compensation significantly influences employee productivity, and simultaneously, work motivation and compensation significantly influence employee productivity. This research implies that the company should continue to enhance motivation and provide fair compensation to optimize employee productivity.